Bringing Thermoelectricity into Reality - Aranguren, Patricia (IntechOpen, 2018)
The disproportionate use of fossil fuels has turned into a serious environmental issue. Thus, we are encountering one of the biggest challenges of the twenty-first century, satisfying the energy demand with respect to the environment. Thermoelectricity is an emerging technology, which contributes to reducing the impact of the use of traditional technologies, harvesting the waste heat, and eliminating the use of refrigerants. The book Bringing Thermoelectricity into Reality covers the current thermoelectric investigations: the study of novel thermoelectric materials, the development of computational models, the design of proper assemblies, and the optimization of thermal designs, as well as novel thermoelectric generators, coolers, and heating applications. This book looks for the definitive thermoelectric applications applied to everyday life.